A nemzetiszocialista népcsoportjog mint kihívás a magyar kisebbségpolitika számára - Vitári, Zsolt (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
After the First World War, the international system of minority protection offered a welcome opportunity for Hungarian governments to demand the rights of numerically significant Hungarian minority groups from neighbouring states beyond the new borders, while at the same time applying a different standard to the domestic nationalities, which were less significant in number but still considered to be assimilated, including the Germans in the first place. Hungarian ethnopolitics was therefore faced with an extraordinary challenge from the collective approach to the so-called Volksgruppenrecht that was becoming increasingly established in Germany, which denied equality between minority and majority members and thus the ability to integrate, since this was considered impossible in view of the marked ethnic differences. The Volksgruppenrecht aroused keen interest and reaction from Hungarian minority rights theorists, who saw it as a threat to Hungarian ethnopolitics and sought to emphasise its inapplicability and invalidity in Hungary. This discourse was significantly linked to the Institute for Minority Research at the University of Pécs and to its director, Ferenc Faluhelyi, who had extensive German connections. This network of contacts not only provided an opportunity to make the Hungarian perspective known in Germany, but also to follow and react to all the developments of the discourse in Germany. This polemic reached its climax with the so-called Vienna Agreement on Ethnic Groups in 1940.